2015
DOI: 10.1158/1535-7163.mct-14-1103
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of a Novel RXR Agonist for the Treatment of Neuroblastoma

Abstract: Neuroblastoma remains a common cause of pediatric cancer deaths, especially for children who present with advanced stage or recurrent disease. Currently, retinoic acid therapy is used as maintenance treatment to induce differentiation and reduce tumor recurrence following induction therapy for neuroblastoma, but unavoidable side effects are seen. A novel retinoid, UAB30, has been shown to generate negligible toxicities. In the current study, we hypothesized that UAB30 would have a significant impact on multipl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…After injection, the mice were randomized to receive vehicle-treated, RA-treated (53 mg/kg/day), or UAB30-treated chow (100 mg/kg/day) (n = 10 mice per group). These dosages were based upon previous in vivo experiments [19, 20, 28]. The flank tumors were measured twice weekly using calipers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After injection, the mice were randomized to receive vehicle-treated, RA-treated (53 mg/kg/day), or UAB30-treated chow (100 mg/kg/day) (n = 10 mice per group). These dosages were based upon previous in vivo experiments [19, 20, 28]. The flank tumors were measured twice weekly using calipers.…”
Section: Methodsmentioning
confidence: 99%
“…These doses were based upon previous data in the literature [19, 20, 28]. The animals were monitored twice daily for neurologic symptoms and followed for overall survival.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel retinoid, 9- cis -UAB30 (UAB30), a synthetic analog of 9- cis -retinoic acid, binds selectively to the retinoid X receptor (RXR) leading to activation of genes involved in induction of differentiation and apoptosis [7, 8]. UAB30 has minimal toxicity compared to other retinoids [7, 911], and has recently been found to be effective in decreasing xenograft tumor growth in neuroblastoma [12]. Investigators have demonstrated the effectiveness of retinoids against adult liver [13] and kidney tumors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have demonstrated the effectiveness of retinoids against adult liver [13] and kidney tumors [14]. These data in neuroblastoma [12], and the prior results with retinoids in adult renal and hepatic malignancies [13, 14], led us to believe that UAB30 may have an effect upon tumorigenicity in rare pediatric renal and hepatic malignancies.…”
Section: Introductionmentioning
confidence: 99%